2012
DOI: 10.1007/s12021-012-9147-0
|View full text |Cite
|
Sign up to set email alerts
|

Volume Estimation of the Thalamus Using Freesurfer and Stereology: Consistency between Methods

Abstract: Freely available automated MR image analysis techniques are being increasingly used to investigate neuroanatomical abnormalities in patients with neurological disorders. It is important to assess the specificity and validity of automated measurements of structure volumes with respect to reliable manual methods that rely on human anatomical expertise. The thalamus is widely investigated in many neurological and neuropsychiatric disorders using MRI, but thalamic volumes are notoriously difficult to quantify give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 74 publications
0
73
0
Order By: Relevance
“…Still, differences in other parameters of segmentation may account for differences among studies. FreeSurfer segmentation of additional subcortical regions, including thalamus and hippocampus, has also been shown to be similar to manual segmentation (Keller et al, 2012; Morey et al, 2009). …”
Section: Discussionmentioning
confidence: 73%
“…Still, differences in other parameters of segmentation may account for differences among studies. FreeSurfer segmentation of additional subcortical regions, including thalamus and hippocampus, has also been shown to be similar to manual segmentation (Keller et al, 2012; Morey et al, 2009). …”
Section: Discussionmentioning
confidence: 73%
“…Ventricles and corpus callosum volumes were generated using the sum of all subregions. FreeSurfer subcortical segmentation showed a high overlap and high volumetric correlations with manual segmentation (Dewey et al, 2010;Fischl et al, 2002;Keller et al, 2012) and high test-retest reliability Morey et al, 2010).…”
Section: Segmentationmentioning
confidence: 99%
“…Validation studies have shown that this automated segmentation procedure corresponds well with manual tracing (e.g., Fischl et al, 2002; Jovicich et al, 2009; Keller et al, 2012; Lehmann et al, 2010; Mulder et al, 2014; Pardoe et al, 2009; Tae et al, 2008; Wenger et al, 2014). FreeSurfer has been used in a large number of studies investigating age-differences in subcortical structures (e.g., Inano et al, 2013; Jovicich et al, 2009; Long et al, 2012; Potvin et al, 2016; Tamnes et al, 2013; Walhovd et al, 2005, 2011; Wenger et al, 2014; Yang et al, 2016).…”
Section: Methodsmentioning
confidence: 81%